PERANCANGAN BALAI PENGEMBANGAN PELATIHAN KERJA KABUPATEN GORONTALO - Mohamad Dwi Sandi Adipu; Muhammad Rijal Syukri; Mohammad Faisal Dunggio (JAMBURA Journal of Architecture, 2023)
ABSTRACT.  Based on Statistics Indonesia data in Gorontalo Province, the unemployment rate in Gorontalo Regency in 2018 was 12,988 out of 397,206 total population, and in 2019 it was 11,761 out of 366,408 total population. According to the most significant level of education attained, Gorontalo Regency’s open unemployment rate in 2019 was 1036 for primary schools, 446 for junior high schools, 2,940 for high schools, and 1,393 for college or higher education. Due to the rising number of unemployed people in Gorontalo Regency, it is crucial to build and design a Vocational Training Development Center in the region that can accommodate job training activities in a higher capacity and fulfill criteria. Under the direction of the Gorontalo Regency Ministry of Manpower and Transmigration, the Vocational Training Center in that region continues to serve as a Vocational Training Center for the Regional Technical Implementation Unit (UPTD). The UPTD Limboto Vocational Training Center, a facility for education and job training that is still performing pretty well, nevertheless has issues, such as the completeness of the rooms, which is not ideal and following accordance with standards, and the limited number of vocational training programs offered. The Vocational Training Development Center was designed using a contemporary architectural approach, prioritizing user demands in order to adhere to standards while also paying attention to the shape of the building design. Keywords: Vocational Training Development Center, Gorontalo Regency ABSTRAK. Berdasarkan Badan Pusat Statistik (BPS) Provinsi Gorontalo, pada tahun 2018 angkan pengangguran di Kabupaten Gorontalo sebesar 12.988 jiwa dari 397.206 jiwa total penduduk , sedangkan pada tahun 2019 angka pengangguran mencapai 11.761 jiwa dari 366.408 jiwa total penduduk. Tingkat pengangguran terbuka (TPT) di Kabupaten Gorontalo pada tahun 2019 menurut pendidikan tertinggi yang ditamatkan yaitu, Pendidikan Sekolah dasar (SD) mencapai 1036 jiwa, Sekolah Menengah Pertama (SMP) mencapai 446 jiwa, Sekolah Menengah Atas (SMA) mencapai 2.940 jiwa, dan perguruan tinggi atau diatas SMA mencapai 1.393 jiwa. Balai Latihan Kerja yang ada di Kabupaten Gorontalo masih merupakan Balai Latihan Kerja Unit Pelaksana Teknis Daerah (UPTD) yang berada dibawah naungan Kementrian Tenaga Kerja dan Transmigrasi Kabupaten Gorontalo. Sebagai wadah pendidikan dan pelatihan kerja yang mash beroprasional dengan cukup baik, UPTD Balai Latihan Kerja Limboto masih memiliki permasalahan, seperti kelengkapan ruang yang belum optimal dan sesuai standar, dan hanya tersedia sedikit program pelatihan kejuruan. Sehingga diperlukan perencanaan dan perancangan Balai Pengembangan Pelatihan Kerja di Kabupaten Gorontalo yang dapat menampung kegiatan pelatihan kerja dalam kapasitas yang lebih besar dan memenuhi standar seiring dengan makin meningkatnya jumlah pengangguran di Kabupaten Gorontalo. Perancangan Balai Pengembangan Pelatihan Kerja ini menggunakan pendekatan arsitektur modern, dimana perancangan Balai Pengembangan Pelatihan Kerja ini mengutamakan kebutuhan pengguna agar sesuai dengan standar dan tetap memperhatikan bentuk desain bangunannya. Kata kunci: Balai, Pelatihan Kerja, Kabupaten Gorontalo